Hepatitis B virus genome diversity in adolescents: Tenofovir disoproxil fumarate treatment effect and HBeAg serocon version. Issue 8 (8th June 2021) - Combet, Christophe; Bhardwaj, Neeru; Hedskog, Charlotte; Podlaha, Ondrej; Gaggar, Anuj; Murray, Karen F.; Mo, Hongmei; Svarovskaia, Evguenia; Zoulim, Fabien
Abstract: More systematic analysis of hepatitis B virus (HBV) genome diversity, linked with tenofovir disoproxil fumarate (TDF) treatment and HBeAg seroconversion, are needed. GS‐US‐174–0115 was a double‐blind, placebo‐controlled, Phase 3, 192‐week clinical trial that evaluated TDF in adolescents with chronic hepatitis B (CHB). HBV full‐genome deep sequencing was performed using Illumina MiSeq at baseline (BL; n  = 85), Week 8 (W8; n  = 80), Week 72 (W72; PBO only, n  = 42), and treatment‐free follow‐up (TDF only, n  = 25). The viral diversity was calculated using Shannon entropy and population nucleotide diversity with a 2% variant cutoff. Our data showed (i) a higher viral diversity in the X region at baseline than the core/polymerase/surface regions, (ii) higher core/surface viral diversity at baseline for patients with seroconversion, (iii) an expected reduction in viral diversity after 8 weeks of TDF treatment, and (iv) a drop in viral diversity at W72 for patients receiving placebo with a seroconversion ( n  = 7). The higher viral diversity in X was associated with higher baseline alanine aminotransferase (ALT) levels ( p  < .001). Patients with greater reduction of diversity at W8 of TDF treatment had higher baseline ALT levels. For placebo patients who seroconverted, the drop in viral diversity at W72 ( p  = .04) coincided with reduction of serum HBV DNA (average change from baseline = −4.10 log10 copies/ml) and unique combinations of variants were enriched in a patient's viral population post seroconversion. The basal core promoter (BCP) variants, A1762T and G1764A, and the pC variant, G1896A, were most often enriched at or after seroconversion.